Relationship Between Workload to the Level of Burnout in Employees of PT Baba Rafi International - Mumtaz, Annisa; Purwanto, Sugeng (PT FORMOSA CENDEKIA GLOBAL, 2024)
The success of a company depends on its ability to manage various types of resources, one of which is human resources (HR). Employee welfare is an important aspect that companies must pay attention to. When a company has high-performance standards and goals, employees work hard to achieve those goals. However, as a company's organizational performance increases, the workload also increases which can lead to burnout. This research aims to find out the role of workload on burnout among PT Baba Rafi International employees. The method used is a quantitative method and involves 40 employees of PT Baba Rafi International. The data obtained was processed using IBM SPSS version 22. The results of this research show that there is a significant role between workload and burnout in PT Baba Rafi International employees.